Synthesis, mechanism and ethylene polymerization catalysis of Ge(iv), Sn(ii) and Zr(iv) complexes derived from substituted β-diketiminates. Issue 65 (23rd June 2016) - Xiao, Xia; Hao, Xiaomin; Bai, Jianliang; Chao, Jianbin; Cao, Wei; Chen, Xia
Abstract : Unusual X-ray characterized crystalline Sn(ii ), Ge(iv ) and Zr(iv ) complexes have been prepared via a salt metathesis and elimination reaction. Abstract : Insertion of LiCH(SiMe3 )2 into the CN bond of the appropriate nitriles RCN afforded dimeric β-diketiminato lithium complexes [LiN(SiMe3 )C(R)C(H)C(R′)N(SiMe3 )]2 (1a, R = R′ = NMe2 ;1b, R = Bu t, R′ = o -C5 H4 N). Lithium salt1a was used as a precursor to react with SnCl2 and GeCl4, respectively, and complexes [ClSnN(SiMe3 )C(NMe2 )C(H)C(NMe2 )N(SiMe3 )] (2 ) and [Cl2 GeNC(NMe2 )C(H)C(NMe2 )N(GeCl3 )] (3 ) were obtained in good yields. By β-diketiminato lithium1b ligand transfer, the cyclo-1, 3-diazasilane heterocyclic complex (4 ) was prepared using1b and ZrCl4 . Unexpectedly, the chelating β-diketiminato backbone in3 acts as a dianionic ligand, whereas in4, the ligand acts as a neutral cyclo-1, 3-diazasilane heterocyclic ring to coordinate with the Zr center. The X-ray structures of2–4 are presented, and reaction pathways for each complex are proposed. Upon activation with methylaluminoxane, complex4 exhibits good activity for ethylene polymerization.